2022
DOI: 10.1093/botlinnean/boac024
|View full text |Cite
|
Sign up to set email alerts
|

From the Mediterranean to the Pacific: re-circumscription towardsNotelaea s.l.and historical biogeography of a generic complex in Oleinae (Oleaceae)

Abstract: Tackling the complicated infrafamilial classification of the economically important Oleaceae requires a piecemeal approach that addresses generic circumscriptions. Here, focusing on the distinct clade formed by the generic complex Nestegis, Notelaea, Osmanthus, Phillyrea, and Picconia within the subtribe Oleinae, we aim to elucidate their boundaries and relationships and to evaluate their biogeographic history in light of their peculiar disjunct distribution in the Macaronesian, Mediterranean, and Pacific Regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 84 publications
(117 reference statements)
2
4
0
Order By: Relevance
“…Notosmanthus in traditionally morphological classification system. As members of Oleinae subtribe, traditional Osmanthus species did not formed a monophyletic group in our phylogenetic inference, which was consistent with previous studies based on DNA barcodes (Guo et al 2011, Yuan et al 2010, Wallander and Albert 2000, Dupin et al 2022). The phylogenetic position of O. austrocaledonicus, distributed in New Caledonian, appeared to be closer to Notelaea and Nestegis species of NNPPO clade than species of major Osmanthus clade.…”
Section: Phylogenetic Analysissupporting
confidence: 92%
See 2 more Smart Citations
“…Notosmanthus in traditionally morphological classification system. As members of Oleinae subtribe, traditional Osmanthus species did not formed a monophyletic group in our phylogenetic inference, which was consistent with previous studies based on DNA barcodes (Guo et al 2011, Yuan et al 2010, Wallander and Albert 2000, Dupin et al 2022). The phylogenetic position of O. austrocaledonicus, distributed in New Caledonian, appeared to be closer to Notelaea and Nestegis species of NNPPO clade than species of major Osmanthus clade.…”
Section: Phylogenetic Analysissupporting
confidence: 92%
“…Leiolea and Sect. Notosmanthus were more closely related to species of other genera such as Chionanthus, Olea, Nestegis, Noronhia and so on, rather than Osmanthus species belonging to other three sections (Yuan et al 2010, Guo et al 2011, Dupin et al 2022. Li et al (2020a) suggested that the East Asian Sect.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notosmanthus . With the application of molecular systematics to this genus, it has been found that Osmanthus is not a monophyletic taxon; for example, sections Leiolea and Notosmanthus have been proven not to belong to Osmanthus (Dupin et al., 2022; Li et al., 2020). While the remaining three sections cannot correctly reflect grouping relationships, our 4‐clade framework provides new insight and suggests that a revision of the sectional classification of Osmanthus is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Chang are classified as ‘vulnerable’ or ‘endangered’ due to declining populations (Melia et al., 2012; Qin et al., 2017; Tamar, 2020). The taxonomy of Osmanthus is controversial due to convergent trait evolution among unrelated species or genera, with molecular approaches aiding the delimitation of intergeneric boundaries (Dupin et al., 2022; Li et al., 2020, 2022). However, within the genus, conflicts persist between the nuclear and plastid gene trees, suggesting the existence of reticulate evolution (Guo et al., 2011; Li et al., 2020; Yuan et al., 2010).…”
Section: Introductionmentioning
confidence: 99%